# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }-a {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } y-{y^{\prime }}^{2} = y^{2} \ln \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+4 {y^{\prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}a y^{\prime \prime } = \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (y^{2}+2 x^{2} y^{\prime }\right ) y^{\prime \prime }+2 \left (x +y\right ) {y^{\prime }}^{2}+x y^{\prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}{y^{\prime }}^{2}-y^{\prime \prime } y = n \sqrt {{y^{\prime }}^{2}+a^{2} {y^{\prime \prime }}^{2}}
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+{y^{\prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y \left (1-\ln \left (y\right )\right ) y^{\prime \prime }+\left (1+\ln \left (y\right )\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y y^{\prime \prime }+\left (x y^{\prime }-y\right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime \prime }+x {y^{\prime }}^{2}+y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {a^{2}}{y} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y^{3}-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {\mathrm e}^{2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+x {y^{\prime }}^{2}-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } y-{y^{\prime }}^{2}+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+4 {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = a {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } y+\sqrt {{y^{\prime }}^{2}+a^{2} {y^{\prime \prime }}^{2}} = {y^{\prime }}^{2}
\] |
✗ |
✓ |
|
\[
{}a y^{\prime \prime } = \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{\prime \prime }+\sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime \prime }+x {y^{\prime }}^{2} = 3 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y y^{\prime \prime }+y^{2} = x^{2} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime } = \sqrt {m \,x^{2} {y^{\prime }}^{3}+y^{2} n}
\] |
✗ |
✗ |
|
\[
{}x^{4} y^{\prime \prime } = \left (x^{3}+2 x y\right ) y^{\prime }-4 y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime }-x^{3} y^{\prime } = x^{2} {y^{\prime }}^{2}-4 y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+4 y^{2}-6 y = x^{4} {y^{\prime }}^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime } = {\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \frac {1}{\sqrt {a y}}
\] |
✓ |
✓ |
|
\[
{}-a y^{\prime \prime } = \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}\sin \left (y\right )^{3} y^{\prime \prime } = \cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } y+\sqrt {{y^{\prime }}^{2}+a^{2} {y^{\prime \prime }}^{2}} = {y^{\prime }}^{2}
\] |
✗ |
✓ |
|
\[
{}x^{2} y y^{\prime \prime }+\left (x y^{\prime }-y\right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y y^{\prime \prime }+4 y^{2} = x^{2} {y^{\prime }}^{2}+2 x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x^{2} y y^{\prime \prime }+\left (x y^{\prime }-y\right )^{2}-3 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y+3 x y^{\prime }+2 y {y^{\prime }}^{2}+\left (x^{2}+2 y^{\prime } y^{2}\right ) y^{\prime \prime } = 0
\] |
✗ |
✗ |
|
\[
{}\left (y^{2}+2 x^{2} y^{\prime }\right ) y^{\prime \prime }+2 \left (x +y\right ) {y^{\prime }}^{2}+x y^{\prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+y^{\prime }+{y^{\prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y \left (1-\ln \left (y\right )\right ) y^{\prime \prime }+\left (1+\ln \left (y\right )\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } y-{y^{\prime }}^{2} = y^{2} \ln \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y^{\prime \prime } y = n \sqrt {{y^{\prime }}^{2}+a^{2} y^{\prime \prime }}
\] |
✗ |
✗ |
|
\[
{}x^{4} y^{\prime \prime } = \left (-x y^{\prime }+y\right )^{3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+2 y^{\prime } = x^{2} y^{\prime }-y^{2}
\] |
✗ |
✗ |
|